Pengaruh Latihan Quick Leap Dan Depth Jump Terhadap Kemampuan Daya Ledak Otot Tungkai Pemain Bolavoli Tunas Mekar Club Kota Pariaman - Muhammad Fauzan Azima; Muhamad Sazeli Rifki; Nuridin Widya Pranoto; Nugroho Susanto (JURNAL STAMINA, 2022)
The problem in this study is suspected to be the low explosiveness of the muscles of Tunas Mekar players. There are various forms of exercise that can improve the explosiveness of the limb muscles including quick leap and depth jump exercises. This type of research is pseudo-experimental research. The population in this study was all Dynamics players who numbered 25 people. Samples were taken with Purposive Sampling technique, so the sample numbered 16 people. Before conducting experimental activities, sample grouping is carried out, in the grouping of samples is determined based on the preparation of rankings or rankings (ordinally matching pairing). This research instrument uses vertical jump test, and the data analysis technique used is testing the hypothesis of t test. From the analysis of data obtained results: (1) After the pre-test hypothesis test and post-test quickleap exercises can be analyzed with the conclusion Ho rejected and Ha received with the value of Thitung (9.38) > Ttabel (2,365). So the conclusion is " There is a significant influence on quickleap exercises on the ability of limb muscles of the player Bolavoli Tunas Mekar". (2) After the pre-test hypothesis test and post-test exercise depth jump circle can be anailisis results with ho conclusions rejected and Ha received with the value of Thitung (7.95) > Ttabel (2,365). So the conclusion is " There is a significant influence on the exercise of depth jump circles on the ability of the limb muscles of the player bolavoli Tunas Mekar"